Controlled Formation of Silicon-Vacancy Centers in High-Pressure Nanodiamonds Produced from an “Adamantane + Detonation Nanodiamond” Mixture - Dmitrii G. Pasternak; Rustem H. Bagramov; Alexey M. Romshin; Igor P. Zibrov; Vladimir P. Filonenko; Igor I. Vlasov (Nanomaterials)
Despite progress in the high-pressure synthesis of nanodiamonds from hydrocarbons, the problem of controlled formation of fluorescent impurity centers in them still remains unresolved. In our work, we explore the potential of a new precursor composition, a mixture of adamantane with detonation nanodiamond, both in the synthesis of nanodiamonds and in the controlled formation of negatively charged silicon-vacancy centers in such nanodiamonds. Using different adamantane/detonation nanodiamond weight ratios, a series of samples was synthesized at a pressure of 7.5 GPa in the temperature range of 1200–1500 °C. It was found that temperature around 1350 °C, is optimal for the high-yield synthesis of nanodiamonds <50 nm in size. For the first time, controlled formation of negatively charged silicon-vacancy centers in such small nanodiamonds was demonstrated by varying the atomic ratios of silicon/carbon in the precursor in the range of 0.01–1%.